Total Synthesis of (+)‐Alsmaphorazine C and Formal Synthesis of (+)‐Strictamine: A Photo‐Fries Approach. (6th April 2021) - Gao, Beiling; Yao, Fengjie; Zhang, Zhaodong; Ding, Hanfeng
Abstract: A bioinspired photo‐Fries/imine capture cascade reaction was developed in continuous‐flow mode, which facilitated the rapid construction of a series of diversely functionalized 2, 7‐heterocycle‐fused tetrahydrocarbazoles, the ubiquitous core structures embedded in strychnos and akuammiline‐type monoterpene indole alkaloids. The synthetic utility of this novel method has been preliminarily explored by the first total synthesis of (+)‐alsmaphorazine C and formal synthesis of (+)‐strictamine in a concise and efficient manner. Abstract : A continuous‐flow photo‐Fries/imine capture cascade process efficiently assembles the 2, 7‐heterocycle‐fused tetrahydrocarbazole framework of strychnos and akuammiline ‐type monoterpene indole alkaloids. Based on this crucial transformation, the first asymmetric total synthesis of (+)‐alsmaphorazine C and formal synthesis of (+)‐strictamine have been accomplished.